Impact of Emphysema Subtypes and Volume on Lung Ventilation and Gas Exchange Functions as Evidenced by Computed Tomography - N. A. Griva; P. V. Gavrilov; I. A. Nikitina; L. D. Kiryukhina; A. N. Narkevich; E. G. Sokolovich (Вестник рентгенологии и радиологии)
Objective: to characterize the relationship between the subtype and volume of pulmonary emphysema on the indicators of lung ventilation and gas exchange functions. Material and methods. The data of radiation and functional studies were analyzed in 50 patients. The inclusion criteria were chronic obstructive pulmonary disease and emphysema, which had been diagnosed by computed tomography (CT) and confirmed by two radiologists; comprehensive pulmonary function studies, including spirometry and body plethysmography, were performed; diffusion capacity was measured using a single-breath method, involving inhalation of carbon monoxide, and a breath hold. Patients with primary pulmonary emphysema, any history of pulmonary surgery, and emphysema concurrent with other lung X-ray syndromes (consolidation, cavity) were excluded. CT was performed with a 1-mm thick slice and standard scanning parameters on Toshiba tomographs (Japan). Pulmonary function was tested using a MasterScreen Body Diffusion expert diagnostic unit (VIASYS Healthcare, Germany) in accordance with the criteria for correct pulmonary functional tests proposed by a joint group of experts from the American Thoracic Society and the European Respiratory Society. Volumetric analysis of emphysema was performed using the Lung Volume Analysis software package (Toshiba, Japan). In the study, there was a predominance of male patients (n = 42 (84%)), mainly in the 61-70 age group. Results. The isolated type of emphysema was rare: centrilobular and paraseptal emphysemas were seen in 3 (6%) and 2 (4%) patients, respectively. The mixed type of emphysema was detected in 90% of cases; 33 (66%) patients having a predominant centrilobular component constituted a large proportion. It was determined that as the volume of emphysema increased, the patency of the airways worsened, the static pulmonary volumes increased, the lungs were hyperinflated, pulmonary gas exchange worsened, the bronchial resistance slightly increased during calm breathing. No statistically significant results were found from the point of view of correlations between the volume of emphysema and other parameters of pulmonary function. Conclusion. An increase in the volume of emphysema deteriorates pulmonary function; the greatest contribution to the overall picture is made by the patients with a mixed type of emphysema with a predominance of the centrilobular component.